Punção venosa periférica com cateter curto guiado por ultrassom: construção de um protocolo assistencial - Bolina, José Ricardo de Oliveira (Universidade do Vale do Rio dos Sinos, 2014)
The process of obtaining peripheral venous access is one of the most present in the daily activities of nurses working at hospitals. The technique of obtaining peripheral venous access ultrasound-guided has been established based on the experiences of insertion of central catheters, showing its benefits in obtaining peripheral venous access in patients considered to be with difficult venous access. OBJECTIVE: To develop a nursing care protocol to puncture with short peripheral venous access catheter ultrasound-guided through a systematic review. MATERIAL AND METHODS: Exploratory study conducted in databases obtained through the descriptors in MeSH/Decs: peripheral Catheterization; Ultrasonic; Vascular Access; Vascular access device. The systematization of information followed the methodology PICO (Patient, Intervention, Comparison, Outcomes) comprising articles written in English, Spanish or Portuguese, from 2004 that were classified according to the degree of recommendation and level of evidence approach to treatment, prevention, etiology and diagnosis system from Oxford Centre for Evidence Based Medicine and Grading of recommendations Assessment, Development and Evaluation - GRADE. All copyrights are preserved. RESULTS: The search resulted in 2,641,799 articles. Among them, 88,899 were from BVS/LILACS, 5,333 from Cochrane Library, 103,212 from ProQuest Nursing, and 1,656,155 from PUBMED/MEDLINE. After using Boolean operators, reading titles and abstracts, and applying inclusion and exclusion criteria, 24 articles resulted. The construction of the protocol followed the recommendations outlined by methodological guidelines Canadian Coordinating Office for Health Technology Assessment (2003); National Institute for Clinical Excellence (2004); Evaluation and Danish Center for Health Technology Assessment (2005); and Cameron et al. (2008). CONCLUSION: The use of ultrasound to guide vascular access procedures ensures accurate visualization of the vessel and of the needle progression. It also reduces the number of attempts, improves success rates of insertion of lancing device, minimizes complications related to puncture errors and reduces insertion time, ensuring greater efficiency. The procedure standardization through a protocol and training program to develop the specific use of ultrasound equipment associated with the puncture technique, with an understanding of indications and limitations of technical and theoretical skills, assists nurses to perform correct indication of resource use.
Keywords: Cateterismo periférico; Ultrassom; Acesso vascular; Dispositivo de acesso vascular; Catheterization peripheral; Ultrasonic; Vascular access; Vascular access device; ACCNPQ::Ciências da Saúde::Enfermagem